2012
DOI: 10.1007/s00431-012-1759-8
|View full text |Cite
|
Sign up to set email alerts
|

Motor coordination impairment and migraine in children: a new comorbidity?

Abstract: Migraine without aura (MoA) could be considered the most frequent form of primary headache in children, associated with many known comorbidities, but only the recent literature has begun to consider the importance of motor impairment linked to the attacks. The developmental coordination disorder (DCD) is a very common problem among children, with a prevalence ranging up to 19 %. The aim of this study was to evaluate the presence of motor coordination impairment in a population of children affected by MoA, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…47 Furthermore, previous studies showed that migraine may disturb sleep architecture, with excessive daytime sleepiness, higher prevalence of cosleeping with family, and disorders in initiating and maintaining sleep in developmental age. 4852 Additionally, migraines may have some impacts on perceptual organizational ability, 53 mood, 54 and motor coordination 55 in school-aged children. Collectively, the interrelationship and influences between migraine and sleep may not only occur in adults but also in adolescents and children.…”
Section: Discussionmentioning
confidence: 99%
“…47 Furthermore, previous studies showed that migraine may disturb sleep architecture, with excessive daytime sleepiness, higher prevalence of cosleeping with family, and disorders in initiating and maintaining sleep in developmental age. 4852 Additionally, migraines may have some impacts on perceptual organizational ability, 53 mood, 54 and motor coordination 55 in school-aged children. Collectively, the interrelationship and influences between migraine and sleep may not only occur in adults but also in adolescents and children.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast OP rats displayed lower SPA endogenous levels after a high-fat diet administration if compared to their OR group counterpart (Levin et al, 1997; Esposito et al, 2012a). Conversely, obesity tends to increase also the prevalence of migraine in all ages of life (Esposito et al, 2012b; Verrotti et al, 2012, 2015). …”
Section: The Role Of Orexin System In Obesitymentioning
confidence: 99%
“…A recent report has suggested a higher prevalence of developmental coordination disorder and borderline motor skills in children affected by migraine,16 that could be related to their cognitive performance, particularly the reduction in perceptual organization abilities found in children suffering from migraine without aura 17. On the other hand, the presence of headache in late adulthood could seem to be related to worse performance on some measures of executive functioning, suggesting that a cognitive impact is not specific to migraine but might be associated with headache in general 18.…”
Section: Introductionmentioning
confidence: 99%